Design of Plate Girder with Corrugated Web - et. al., Nivedha D.G.S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The corrugated steel plate is to increase the shear capacity of the web of large plate girders. Present paper deals with the calculation of buckling strength of a plate girder considering rectangular, trapezoidal and sinusoidal web plate. The finite element analysis of the plate girder is carried out using ANSYS software. The results obtained from analysis are then compared with the plate girder with plane web of uniform depth. The result of Finite Element Analysis conducted as part of this investigation suggest that the strength is overestimated, at least in part because of the shear behavior to the presence of imperfections in the web.